Comparison of the 7-day CO-Synch and 8-day estradiol-based protocols for estrus synchronization and timed artificial insemination in suckled Bos taurus cows - Rodriguez, Alejandro Martin; Maresca, Sebastian; Lopez Valiente, Sebastian; Bilbao, María Guillermina; Moran, Karen D.; Bartolome, Julián Alberto; Pratt, Scott L.; Long, Nathan M. (Elsevier, 2023)
Two experiments were conducted to compare, follicle diameter (FD) on Day −1, corpus luteum (CL) area on Day 7, progesterone (P4) concentration on Day 7 and 18, pregnancy per timed artificial insemination (TAI) on Day 30, and pregnancy loss (PL) between Days 30 and 60 after TAI (TAI, Day 0) using two different synchronization protocols. In Experiment 1, Angus cows (n = 1148) were randomly assigned to either 7-d progesterone CO-Synch (7-d CO-Synch) or 8-d progesterone + estradiol (8-d P + ES) synchronization protocols for TAI. On Day −10, cows in the 7-d CO-Synch treatment group (n = 574) received a progesterone-releasing intravaginal device (PIVD; 0.5 g P4) and GnRH (0.105 mg), on Day −3 the PIVD was removed and cows received cloprostenol (0.150 mg), then, on Day 0 (64 h after PIVD removal), cows received GnRH (0.105 mg) and were TAI. On Day −10, cows in the 8-d P + ES treatment group (n = 574) received a PIVD (0.5 g P4) and estradiol benzoate (2.0 mg), on Day −2 the PIVD was removed, and cows received cloprostenol (0.150 mg) and estradiol cypionate (0.5 mg), then, on Day 0 (48 h after PIVD removal), cows were TAI. Pregnancy per TAI was determined on Days 30 and 60. In a subset of cows (7-d CO-Synch, n = 41; 8-d P + ES, n = 40), serum P4 concentration was evaluated on Day 18. In Experiment 2, anestrus (n = 34) and cyclic (n = 34) suckled beef cows were selected and submitted at random on Day −10, to either 7-d CO-Synch or 8-d P + ES treatment groups. Follicle diameter on Day −1, CL area, and serum P4 concentration on Day 7 were determined. In Experiment 1, pregnancy per TAI on Day 30 did not differ (7-d CO-Synch = 48.9%; 8-d P + ES = 45.6%) between treatments but it was greater for cows with BCS ≥5 (P < 0.01). Pregnancy loss between Days 30 and 60 did not differ between treatment groups but tended to be greater in cows with BCS <5.0 (P < 0.1). In a subset of cows, serum P4 concentration on Day 18 did not differ between treatment groups but tended to be lower (P < 0.1) in cows that had PL between Days 30 and 60 compared to cows that had no PL. In Experiment 2, FD tended to be greater (P < 0.1) and CL area was greater (P = 0.05) in anestrus cows from 7-d CO-Synch treatment. In cyclic cows, the treatment did not affect the FD or CL area. In conclusion, there was no difference in pregnancy per TAI on Day 30 and PL between Days 30 and 60 between cows using 7-d CO-Synch + PIVD or 8-d estradiol-based + PIVD protocols for estrus synchronization and TAI.